Strategies of coping with the difficulties of young people with mental disorders who have left institutional care for children and youth - Alma Lileikienė (Social Welfare: Interdisciplinary Approach, 2012)
Coping with the difficulties according to the model of coping process created by Moos and Schaefer (Bagdonas (managing editor), 2007, p. 198) depends on personal features, social resources, ability to evaluate the situation. If there are no resources required, a person cannot employ suitable coping strategies. The more person’s mental health is disordered the more his/her coping is directed towards emotions and less adaptive behaviour. It is also reflected in coping with the difficulties among persons with mental disorders who grew up under institutional care. The article generalizes the researches on how persons with mental disorders who have left institutional care for children and youth cope with their difficulties, what coping strategies they use.